2012
DOI: 10.1371/journal.pone.0048159
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium breve with α-Linolenic Acid and Linoleic Acid Alters Fatty Acid Metabolism in the Maternal Separation Model of Irritable Bowel Syndrome

Abstract: The aim of this study was to compare the impact of dietary supplementation with a Bifidobacterium breve strain together with linoleic acid & α-linolenic acid, for 7 weeks, on colonic sensitivity and fatty acid metabolism in rats. Maternally separated and non-maternally separated Sprague Dawley rats (n = 15) were orally gavaged with either B. breve DPC6330 (109 microorganisms/day) alone or in combination with 0.5% (w/w) linoleic acid & 0.5% (w/w) α-linolenic acid, daily for 7 weeks and compared with trehalose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 69 publications
(88 reference statements)
0
22
0
Order By: Relevance
“…These actions are characteristic of specialized pro-resolving mediators37 and define these novel n-3 DPA products as immunoresolvents. In view of the role of lipid mediators in inflammation and its timely resolution1437, the n-3 DPA metabolome documented herein may mediate some of the beneficial actions associated with probiotic dietary supplementation40. Moreover, these new n-3 immunoresolvents may also serve as a compensatory mechanism in people with elevated n-3 DPA levels and lower circulating DHA levels21 to compensate for losses in DHA SPM-regulated leukocyte-mediated tissue damage and timely resolution of acute inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…These actions are characteristic of specialized pro-resolving mediators37 and define these novel n-3 DPA products as immunoresolvents. In view of the role of lipid mediators in inflammation and its timely resolution1437, the n-3 DPA metabolome documented herein may mediate some of the beneficial actions associated with probiotic dietary supplementation40. Moreover, these new n-3 immunoresolvents may also serve as a compensatory mechanism in people with elevated n-3 DPA levels and lower circulating DHA levels21 to compensate for losses in DHA SPM-regulated leukocyte-mediated tissue damage and timely resolution of acute inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…However, in specific dietary supplementation, ALA increased tissue concentrations of EPA and DHA174142, in fact, we have previously demonstrated that supplementing an ALA enriched diet with B. breve NCIMB 702258 and B. breve DPC 6330 increased tissue concentrations of EPA, docosapentaenoic acid and DHA, compared with dietary ALA alone1719, favouring DHA biosynthesis. Flaxseed has thus emerged as an important functional food ingredient, as it is one of the richest sources of ALA (1 tablespoon of flaxseed oil contains ~8 g ALA)43.…”
mentioning
confidence: 87%
“…However, in maternally separated rats, dietary supplementation with fish oil reduces neither the response to colon distension nor the level of pro-inflammatory cytokines in colonic tissue (van Diest et al, 2015). Another study combined the supplementation with CLA and probiotics ( B.breve DPC6330) (Barrett et al, 2012). Groups of 15 rats were either separated from their mothers or not, and fed with probiotic, probiotic together with LA and ALA, or placebo.…”
Section: Pufas In Irritable Bowel Syndromementioning
confidence: 99%
“…Groups of 15 rats were either separated from their mothers or not, and fed with probiotic, probiotic together with LA and ALA, or placebo. The supplementation provided significant changes in lipid composition in the rats' serum, colonic tissue and prefrontal cortex, but failed to clearly change the colonic hypersensitivity measured by colon distension (Barrett et al, 2012). Of note, the use of human intestine bacteria ( B. breve, strain DPC6330) affected the FA metabolism in maternally separated rats to a greater extent than in non-separated animals.…”
Section: Pufas In Irritable Bowel Syndromementioning
confidence: 99%